Normatividad de productos agroecológicos colombianos exportables (2021)
This work has as its scope an exploratory research with some descriptive scope, that is, that the first approach will be made to a specific topic, in this case the regulations for the market of exportable Colombian agroecological products. Initially, a search for information from the international environment will be done, based on IFOAM's organic certification guidelines and Codex Alimentarius organic production guidelines, collection of internationally recognized standards, codes of practice, guidelines and other recommendations related to food, food production and food safety. Subsequent to this, the characteristics of agro-ecological products developed in Colombia will be specifically deepened, after this, Colombia's participation in the production, export and marketing of agroecological products will be demonstrated, and finally the regulations established by national and international organizations for the marketing of agroecological products at the international level will be described.